Correlation of Duke Treadmill Score with Coronary angiographic Findings in Patients with Stable Ischemic Heart Disease - Shehzad Ahmad, Asif Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the correlation of Duke treadmill score with angiographically determined obstructive coronary artery disease (CAD) Study design: observational cross sectional study, comparative type Place and duration: The study was done at Cardiac Center Bahawalpur from August 2020 to July 2021. Methods: The patients who had stable angina and underwent exercise tolerance testing as well as coronary angiography were included in the study. The data was collected on a predesigned proforma. The difference in the prevalence of obstructive CAD with regards to Duke treadmill score (DTS), gender, diabetes mellitus, hypertension, smoking and family history was determined with Chi square test using SPSS 20; ap value of < 0.05 was taken as significant. Results: Total 71 patients were enrolled for study. Mean ageof the participants was 48.25 ± 8.7 years. It was a male dominant population. A significant difference in the prevalence of obstructive CADwas noted in low, intermediate and high risk groups according to DTS. The prevalence of obstructive coronary artery disease was not significantly different with regards to gender, diabetes mellitus, hypertension, smoking and family history. However obstructive CAD was more prevalent in those who presented with typical angina as compared to those who had atypical symptoms. Conclusion: Obstructive CAD significantly differs in low, intermediate and high risk groups according to DTS. Keywords: Duke treadmill score, coronary artery disease